Development of Personal and Professional Culture as the Basis for Engineer’s Effective Activities - Revin, Ivan; Susimenko, Elena; Revina, Elena; Garaeva, Marina (International Journal of Criminology and Sociology, 2022)
The article deals with the specific character of modern engineering education, its meaning seen by the authors as the development of a competent specialist, who is well aware of complex socio-cultural circumstances, responsible and able to act professionally in the rapidly changing environment of science and industry. Such specialist is the bearer of personal and professional culture, being a special type of mental activity arrangement, which manifests itself and finds realization in the professional functioning, which embodies various apprehended, adopted, reproduced and newly elaborated patterns of culture. The paper aims at specifying the concept of “personal and professional culture of an engineer” from the viewpoint of a qualitative characteristic of consciousness and vital activity and behavior. In this study, the authors for the first time structurally characterize this concept by its reasonable analysis in the unity of all such components as general culture, communicative culture, information-methodological culture, culture of personal improvement, professional competence, culture of thinking and creative qualities. The discussion substantiates the technology of effective social and natural interaction, contributing to the development of a cultural-like techno sphere, which encourages self-realization of an engineer in his activity as a special area of culture (to carry out his assignment), and therefore can be the equivalent of his social dignity. Personal and professional culture is studied as a special qualitative characteristic of human consciousness and life, reflecting the attained level and character of the development of professionally significant personal qualities of the specialist, representing the system of his values and emotional attitudes, which affect the efficiency of his engineering activities. The authors suggest its integrative model with invariant indicators.